Соціально-економічні аспекти формування соціального капіталу в Україні - Волчкова, Г. К.; Volchkova, H. (Вінниця, Нілан-ЛТД, 2018)
Розглянуто основні складові соціального капіталу, проаналізовано вплив довіри до державних інституцій на формування соціального капіталу суспільства. The main components of social capital are considered, the influence of trust in state institutions on the social capital formation in society is analyzed.
Social and economic aspects of social capital formation in Ukraine
Keywords: соціальний капітал; індекс процвітання; довіра до інституцій; social capital; prosperity index; trust in institutions